2015
DOI: 10.1038/mp.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament subunits are integral components of synapses and modulate neurotransmission and behavior in vivo

Abstract: Synaptic roles for neurofilament proteins have rarely been considered. Here, we establish all four neurofilament subunits as integral resident proteins of synapses. Compared to the population in axons, neurofilament subunits isolated from synapses have distinctive stoichiometry and phosphorylation state, and respond differently to perturbations in vivo. Completely eliminating neurofilament proteins from brain by genetically deleting three subunits (α-internexin, NFH and NFL) markedly depresses hippocampal LTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 42 publications
8
134
0
1
Order By: Relevance
“…NF assembly confers significant proteolytic resistance to NF subunits because deletion of three NF subunits leads to degradation of the fourth subunit (Yuan et al 2015c). Moreover, multiple in vivo pulse-labeling studies indicate that NFs are extraordinarily stable in axons (half-life of ~55 d) (Nixon and Logvinenko 1986; Yuan et al 2009; Rao et al 2012).…”
Section: Nf Protein Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…NF assembly confers significant proteolytic resistance to NF subunits because deletion of three NF subunits leads to degradation of the fourth subunit (Yuan et al 2015c). Moreover, multiple in vivo pulse-labeling studies indicate that NFs are extraordinarily stable in axons (half-life of ~55 d) (Nixon and Logvinenko 1986; Yuan et al 2009; Rao et al 2012).…”
Section: Nf Protein Degradationmentioning
confidence: 99%
“…2002). Using multiple independent approaches, however, Yuan and colleagues recently provided definitive evidence both for the presence of NF proteins in synapses and for a role for these proteins in synaptic function (Yuan et al 2015c). NF assemblies isolated from synapses are distinctive.…”
Section: Functions Of Nf Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly specialized composition of synapses includes not only the well characterized vesicular and protein receptor machinery supporting neurotransmission but also a specialized cytoskeleton important for delivering, inserting, and recycling synaptic components. Like other domains in a neuron, the cytoskeleton in synapses is composed of microtubules, actin filaments, the spectrin-rich membrane skeleton, and as recently shown, NF assemblies [191, 193]. Evidence is also emerging that the cytoskeleton, and especially the NF scaffold, acts as a docking platform to organize the topography of organelles within different neuronal compartments.…”
Section: Introductionmentioning
confidence: 99%
“…28 In transgenic mice, the specific deletion of NEFM, but not of NEFL or NEFH, amplified the D1R-mediated motor responses to cocaine and caused the redistribution of post-synaptic D1R to the plasma membrane from the endocytic-recycling compartment. 29 In brain and extraneuronal cancer NEFM, NEFL and NEFH play a role as onco-suppressors because their epigenetic silencing affects cell proliferation and correlates with aggressiveness and prognosis. [30][31][32][33] Similar to other upregulated genes in human ZG, we found that NEFM suppresses aldosterone secretion and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%